The third wheel - Kinney, Jeff (Kinney, Jeff. Diary of a wimpy kid, 2012)
With Valentine's Day fast approaching, Greg desperately searches for a date for the school dance. Although he manages to find someone to go with, his best friend is left on the sidelines, setting the stage for a humorous and unexpected turn of events.